2022
DOI: 10.2217/bmm-2022-0056
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hemato-Immunological Biomarkers Associated With Increased Covid-19 Mortality in the Latino Population

Abstract: Introduction: COVID-19 hospitalizations and deaths have raised the need of identifying prognostic factors for medical decision-making. Methods: Observational, retrospective study analyzing 191 COVID-19 patients' serum inflammatory biomarkers. Results: The median age was 48.7 ± 12.7 years, 75.9% being men. Overweight/obesity was the most common comorbidity in 83.8% of patients. 44.5% had moderate disease followed by 43.5% with severe disease. The mean percentage of pulmonary damage was 53.4% ± 28.7. Serum leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Other studies reinforce the association of biochemical markers and increased COVID-19 mortality in the Latino population, Ríos et al published that the Leukocyte-to-Lymphocyte ratio, NLR, platelet-to-lymphocyte ratio, and nutritional index all were mortality predictors for COVID-19 [ 21 ]. Rosa et al [ 2 ] found that non-survivors had significantly increased CRP, neutrophil count, NLR, ferritin, and AST compared to survivors.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Other studies reinforce the association of biochemical markers and increased COVID-19 mortality in the Latino population, Ríos et al published that the Leukocyte-to-Lymphocyte ratio, NLR, platelet-to-lymphocyte ratio, and nutritional index all were mortality predictors for COVID-19 [ 21 ]. Rosa et al [ 2 ] found that non-survivors had significantly increased CRP, neutrophil count, NLR, ferritin, and AST compared to survivors.…”
Section: Discussionmentioning
confidence: 83%
“…The presence of obesity, diabetes, hypertension, and CKD increases the mortality risk of COVID-19 [ 2 , 19 , 20 ], the mortality risk sharply increases with two or more comorbid diseases [ 19 ]. The Mexican population is at high risk of developing severe COVID-19 due to the high prevalence of overweight, with 70% of the population being overweight [ 21 ]. Cervantes et al [ 16 ] performed a study of Hispanic 82 patients with COVID-19 on the USA-Mexico border, where he sought to evaluate the factors associated with COVID-19 severity and mortality where they reported hypertension (48.8%) and DM (39%), as well as advanced age, fever, and low SpO2, but no other biochemical value.…”
Section: Discussionmentioning
confidence: 99%
“…The need for invasive mechanical ventilation and an NLR ≥ 9 significantly increased the odds of dying from COVID-19 ( 37 ). Subsequently, some studies involving the native Mexican Latino population have suggested cut-off values of NLR ranging from 5.43 (AUC 0.80) to >10.0 (OR 2.2) as predictors of poor outcome ( 39–42 ). We determined that dNLR was more predictive than NLR in the current study.…”
Section: Discussionmentioning
confidence: 99%